P154 SINGLE-CELL ANALYSIS OF T CELL PATHOGENESIS IN PEDIATRIC CROHN'S DISEASE. (7th February 2019) - Zheng, Hengqi; Ordovas-Montanes, Jose; Doran, Benjamin; Yu, Alison; Betz, Kayla; Cribbin, Kayla; Tkachev, Victor; Colonna, Lucrezia; Furlan, Scott; Dean, Carol; Bratrude, Brandi; Suskind, David; et al.
Abstract: Background: Crohn's disease (CD) is chronic complex autoimmune condition characterized by inflammation of the gastrointestinal tract. Pediatric CD diagnosed in patients younger than 20 years of age comprises 30% of all diagnosed CD. There is significant data to suggest that CD may represent an inappropriate T-cell mediated immune response towards self-antigens and commensal microbiota in a genetically susceptible host. To understand the T cell-mediated pathogenesis in pediatric CD we performed scRNA-seq analysis and concurrent flow cytometric analysis on mucosal biopsies from the multiple locations along the gastrointestinal tract and paired peripheral blood lymphocytes in pediatric CD and compared these to matched samples from patients with pediatric Functional Gastrointestinal Disorders (FGID). ScRNA-seq allows us to use a systematic approach to the classification of T cell subsets to understand the pathogenesis behind disease development and progression. Methods: Patients were enrolled on the PREDICT trial (Clinicaltrials.gov# NCT03369353) at Seattle Children's Hospital, Seattle WA, and peripheral blood as well as endoscopic biopsies were obtained. We performed scRNA-seq on cells from the epithelium and lamina propria from biopsies of duodenum, terminal ileum and colon, and paired peripheral blood T cells (magnetically separated using a Miltenyi CD3 negative-selection column) of treatment naïve pediatric CD patients and age-matched endoscopic and histologically normal tissue from pediatric FGID comparisons. ScRNA-seq was performed using the 3' 10x Genomics platform and flow cytometry was performed on a BD Fortessa and analyzed using FloJo analysis software. Results: 16 CD patients and 16 FGID patients have been enrolled on PREDICT thus far. To date, we have performed scRNA-seq on 41, 788, 14, 687, and 28, 971 cells from the lamina propria layer of the duodenum, terminal ileum, and colon respectively from 6 children (n=3 CD, n=3 FGID comparisons). (Figure 1) ScRNASeq has identified distinct cellular clustering in CD versus FGID and has identified unique activation markers as well as transcriptional regulators in CD patients. We track how T cell states exist and contribute to disease phenotype in various locations of the gastrointestinal tract, as well as in peripheral blood in order to uncover potential biomarkers. These differences in local and distributed immune response provide key insights into disease-specific tissue remodeling, and give new understanding into the genetic components responsible for driving pathogenic T cell states. Conclusions: Single cell evaluation of pediatric CD patients in PREDICT has identified unique pathways and disease-specific transcriptional regulators when compared to non-immune gastrointestinal disorders.